Misinformation and de-contextualization: international media reporting on Sweden and COVID-19 - Rachel Elisabeth Irwin (BMC, 2020)
Abstract In the first month of the 2020 COVID-19 pandemic, Sweden took the same strategy as most other countries, working to "flatten the curve," by slowing transmission so that the healthcare system could cope with the disease. However, unlike most other countries, much of Sweden's implementation focused on voluntary and stepwise action, rather than legislation and compulsory measures, leading to considerable attention in the international media. Six main narratives emerged in the international media reporting on Sweden during the first month of the COVID-19 pandemic: (1) Life is normal in Sweden, (2) Sweden has a herd immunity strategy, (3) Sweden is not following expert advice, (4) Sweden is not following WHO recommendations (5) the Swedish approach is failing and (6) Swedes trust the government. While these narratives are partially grounded in reality, in some media outlets, the language and examples used to frame the story distorted the accuracy of the reporting. This debate examines the ways in which international media both constructs and represents a pandemic, and the implications for how researchers engage with news and social media. Cross-country comparison and the sharing of best practice are reliant on accurate information. The Swedish example underlines the importance of fact checking and source critique and the need for precision when presenting data and statistics. It also highlights limitations of using culture as an explanation for behavior, and the pitfalls of evaluating policy during a pandemic.